2009 IEEE International Symposium on Circuits and Systems 2009
DOI: 10.1109/iscas.2009.5118043
|View full text |Cite
|
Sign up to set email alerts
|

Learning EEG-based spectral-spatial patterns for attention level measurement

Abstract: Abstract-In our every day life, our brain is constantly processing information and paying attention, reacting accordingly, to all sorts of sensory inputs (auditory, visual, etc.). In some cases, there is a need to accurately measure a person's level of attention to monitor a sportsman performance, to detect Attention Deficit Hyperactivity Disorder (ADHD) in children, to evaluate the effectiveness of neuro-feedback treatment, etc.In this paper we propose a novel approach to extract, select and learn spectral-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…Using two filters in a row including filter bank (FB) and common spatial pattern (CSP), they extracted spectral-spatial features from EEG which was recorded using multiple electrodes placed in various brain regions. Then, the extracted features were sent to a fisher linear discriminant (FLD) classifier for classification task [23]. Their approach outperformed the conventional methods based on only spectral features.…”
Section: Introductionmentioning
confidence: 99%
“…Using two filters in a row including filter bank (FB) and common spatial pattern (CSP), they extracted spectral-spatial features from EEG which was recorded using multiple electrodes placed in various brain regions. Then, the extracted features were sent to a fisher linear discriminant (FLD) classifier for classification task [23]. Their approach outperformed the conventional methods based on only spectral features.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, such tools might lead to improved individualized NF features, with a higher SNR, going beyond heuristics like Individualized Alpha Frequency (IAF) (Bazanova et al, 2010). Moreover, ML algorithms are also used to automatically identify functionallyspecific cortical sources, e.g., SMR sources (Blankertz et al, 2008, Vidaurre et al, 2012 or attention-related sources (Hamadicharef et al, 2009). Such sources are defined as the individual EEG channels (Lal et al, 2004;Arvaneh et al, 2011) or combination of channels, i.e., spatial filters (Blankertz et al, 2008;Lotte & Guan, 2011;Samek et al, 2014), which record the greatest modulation of EEG activity during a given task.…”
Section: Adapting the Neurophysiological Featuresmentioning
confidence: 99%
“…Berka et al developed one of the first commercial systems, known as B-Alert [6], to detect states of attention (high-engagement, low-engagement, relaxed wakefulness, and sleepy) in real time by a medical grade EEG device, but were not configured to detect divided attention. Hamadicharef et al were the first to apply the filter bank common spatial pattern (FBCSP) [8] algorithm to an attention task with EEG data. They found that the FBCSP method classified up to 89.4% between states of attention and relaxation using a 15-channel medical grade EEG device.…”
Section: Related Workmentioning
confidence: 99%